Formação docente continuada e a espiritualidade: uma abordagem a partir do último Foucault - Menegat, Cezar (2017)
The present dissertation deals about the continuous teaching formation and the spirituality based on the last Foucault written ideas. The continuous teaching formation has been a concern in different schools instituitions levels and in the educational research areas as well. In the various stages of the brazilian education history there were always attempts to try to answer challenges according to the arising problems. At present time the continuous teaching formation is growing in importance due to the existing problems in the private and public educational schools. It is suggested in this research as an answer of this challenge the use of spirituality in the context of new approaches in our society of information and technology and its importance to educate the new generations based on the latest Foucault written papers, mainly those carried on at Collège de France, in 1982 with the title “The hermeneutic of de subject”.The option to use the latests Foucault written ideas is because their importance and their currenlty use by scholars mainly in the educational área. This paper is based on a literature search methodology. Some aspects of the brazilian education analysis are presented with the purpose of understanding the contexts which comprehend the educational processes with emphasis in the importance of the individuals formation. Besides, starting by the latest Foucault theory mainly “The subject hermeneutic” it is approached the spirituality theme mainly in the teological field as a way to form the new generations. A reflexion on self-care having the dialogue between Socates and Alcebíades as a starting point. At last is is presented a continuous teaching formation as an educational chalenge pointing out the school importance at the nowadays society position, as well the role of the teacher in the teaching process.